A five-year review of basic psychological need satisfaction, family harmony, social networking sites usage and psychological distress among university students - Jie, Du; Hasbullah, Muslihah; Wan Abdullah, Wan Arnidawati; Kahar, Rojanah (HRMARS, 2024)
Globally, in the last 5 years, studies conducted on different samples of university students have identified a moderate to high prevalence of psychological distress (PD) such as depression, anxiety and stress. Family harmony (FH) and social networking sites (SNS) usage also become the important risk and protective factors for PD through students’ basic psychological needs satisfaction (BPNS). The aims of the present review were (i) to determine the prevalence of PD among university students and (ii) to elucidate the relationship between PD, BPNS, FH, and SNS. The findings demonstrated the heterogeneity of the PD observed in university students in the aftermath of COVID-19. Results suggest that Satisfaction of basic psychological needs (BPNS) can protect university students against PD, while family harmony (FH) and usage of social networking sites (SNS) are their common important influencing factors which can have serious detrimental effects on their health and well-being. While most of the studies consider a range of negative effects from family and internet use as risk factors, there are fewer research which investigate FH and SNS usage as protective factors. Future research could explore how family harmony, social networking site usage, and basic psychological needs satisfaction operate across diverse cultural and contextual backgrounds, as these factors may have varying effects on psychological distress depending on cultural norms, values, and family dynamics. Such research could contribute to developing targeted, contextually relevant interventions that foster resilience and promote well-being among university students globally, addressing the nuanced needs of different student populations.